Towards sustainability: The relationship between foreign direct investment, economic freedom and inclusive green growth - Isaac Kwesi Ofori; Francesco Figari; Nathanael Ojong (African Governance and Development Institute (AGDI), 2023)
This study contributes to the environmental and socioeconomic sustainability literature by examining three important issues. First, the study examines the effects of foreign direct investment (FDI) and economic freedom on inclusive green growth (IGG) in sub-Saharan Africa (SSA). Second, we investigate whether economic freedom interacts with FDI to promote IGG. Third, we identify minimum the thresholds required for economic freedom to cause FDI to foster IGG. The findings are based on macro data for 20 SSA countries. Evidence, based on instrumental variable regression, show that, unconditionally, FDI is not statistically significant for promoting IGG. Second, the study finds that SSA's 'Mostly unfree' economic architecture conditions FDI to reduce IGG. Third, results from our threshold regression reveal that the minimum threshold required for economic freedom to cause FDI to foster IGG is 66.2% (Moderately free). The study sheds new light on investments necessary for SSA's economic architecture to form relevant synergies with FDI to promote IGG.
Keywords: F21; F6; H1; P1; O55; Q01; Q56; 330; Economic Freedom; FDI; Government Integrity; Inclusive Green Growth; Sustainable Development; sub-Saharan Africa